Edge Computing : Architecture and Applications - Šlambor, Jakub (2023)
This thesis examines the topic of Edge Computing. The aim of this thesis is to investigate the application of Edge Computing to different application domains such as IoT, healthcare, etc., and to develop a prototype application that allows the comparison of Edge Computing solutions with the traditional approach. Edge Computing is first defined and categorized, the development and trends in the field are shown, and the hardware and software of a typical Edge computer are described, as is the security of Edge systems. A case study in a startup Herohero is conducted, and an application prototype using Cloudflare Workers is deployed to production, fulfilling the aim and answering the questions of what the purpose and business case characteristics of using Edge Computing are and what are the benefits and drawbacks of utilizing the Edge for the deployment of a Web application. The methods of processing used to achieve the goal of the thesis include the analysis of scientific documents and internet sources, comparison of the traditional and Edge approach, and gathering metrics to assess them both.